2019
DOI: 10.1016/j.foodchem.2018.12.119
|View full text |Cite
|
Sign up to set email alerts
|

Towards honey authentication: Differentiation of Apis mellifera subspecies in European honeys based on mitochondrial DNA markers

Abstract: Honey is the natural sweet substance produced by Apis mellifera honeybees in Europe. Depending on the country/region, the A. mellifera subspecies native to Europe belong to three different lineages: A (A. m. iberiensis), M (A. m. iberiensis and A. m. mellifera) and C (A. m. ligustica and A. m. carnica). In this work, two DNAbased approaches were developed with the aim of entomological authentication of European honeys. A cytb specific PCR assay was proposed to identify A-lineage honeybees, while a second metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 29 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…In such instances, when trading queens or colonies across national borders, queen origin needs to be verified. Additionally, authentication of the genetic origin of bee products in terms of a certifiable native bee label, could help beekeepers to better market their hive products [26]. Thus, to implement effective border control, increase economic value of bee products and to support informed conservation and breeding management decisions across Europe, there is a demand for diagnostic genetic test to reliably infer the subspecies of origin.…”
Section: Introductionmentioning
confidence: 99%
“…In such instances, when trading queens or colonies across national borders, queen origin needs to be verified. Additionally, authentication of the genetic origin of bee products in terms of a certifiable native bee label, could help beekeepers to better market their hive products [26]. Thus, to implement effective border control, increase economic value of bee products and to support informed conservation and breeding management decisions across Europe, there is a demand for diagnostic genetic test to reliably infer the subspecies of origin.…”
Section: Introductionmentioning
confidence: 99%
“…DNA-based identification has the potential to reduce processing time and increase the level of discriminated species [21]. Soares et al [22] reported that they extracted the DNA markers and the yield and purity of the extracts were evaluated by UV spectrophotometry; this method was validated successfully with honey of known origins and applied to the entomological authentication of 20 commercial samples from different European countries.Spectroscopic techniques, such as Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy, are alternative methods for authenticating honey and these techniques are reliable, practical and not time-consuming. FTIR spectroscopy is sensitive to the chemical composition of the sample, and when coupled with multivariate statistical analysis, it provides accurate results in determining the botanical origin of honey [9].…”
mentioning
confidence: 99%
“…DNA-based identification has the potential to reduce processing time and increase the level of discriminated species [21]. Soares et al [22] reported that they extracted the DNA markers and the yield and purity of the extracts were evaluated by UV spectrophotometry; this method was validated successfully with honey of known origins and applied to the entomological authentication of 20 commercial samples from different European countries.…”
mentioning
confidence: 99%
“…Most of the current studies focus on two aspects: one is the identification of floral honey origin markers, including chiral volatile compounds (e.g., linalool, γ-Nonalactone, farnesol and acetovanillone) (Castro-Vázquez et al, 2014), succinate and kynurate (Consonni et al, 2019), specific gene fragments (Soares et al, 2019), proteins (allergens, venomlike proteins, antibacterial properties, royal jelly proteins, serine proteases, floral nectar chitinase) (Song et al, 2019), free amino acids (Azevedo et al, 2017), 3-phenyllactic acid, 2′-methoxyacetophenone, 2-methoxybenzoic acid and 4-hydroxyphenyllacetic acid (Burns et al, 2018), 5-hydroxymethylfurfural (Turkut et al, 2018). The other is the determination of honey adulterants such as starch syrup, inverted syrup, starch or inverted syrup fed to bees, and low-quality honey added to high-priced honey (Naila et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Methods used to identify targeted markers of adulteration/authenticity include automatic pulse voltammetric electronic tongue (Sobrino-Gregorio et al, 2018), NMR-based metabolomic approach (Consonni et al, 2019), rapid evaporative ionization mass spectrometry (H. , UPLC-QToF MS (Jandrić et al, 2017), ICP-MS/ICP-OES (Enrique et al, 2018), SPME-GC-MS (Verzera et al, 2014), GC-MS combined with a chemometric approach (Azevedo et al, 2017), GC-IMS and FT-MIR (Schwolow et al, 2019), LC-MS/MS (Burns et al, 2018), FTIR-ATR spectroscopy (Kasprzyk et al, 2018), NIR spectroscopy (Guelpa et al, 2017), comprehensive proteomic analysis (Erban et al, 2019), semiconductor based sequencing (Utzeri et al, 2018), DNA-barcoding approach (Soares et al, 2018), conventional and real-time PCR (Laube et al, 2010;Soares et al, 2019), and other advanced molecular, chromatographic, and spectroscopic analytical methods have been established with their own pros and cons (Naila et al, 2018). PCR-based methods offer reduced time of analysis and increased level of species discrimination, and hence represent suitable alternatives for authentication of honey and detection of honey adulterants (Soares et al, 2017).…”
Section: Introductionmentioning
confidence: 99%